Framework para o Desenvolvimento de Aplicações Orientadas à Agricultura de Precisão Baseadas em Redes De Sensores e Atuadores Sem Fios - Ricardo Jorge Silva Gama Nogueira (2014)
Historically, agriculture presents itself as one of the oldest and most important economic activities, based on techniques that aim to grow plants and get raw materials essential to human life as food and energy. For the last two centuries has been a major expansion of this activity resulting from the growth of world population and its needs.This expansion is strongly related to the technological evolution that in each step allows agriculture to become a more efficient activity. Thus, the concept of Precision Agriculture arises with the use of high-tech equipment to produce crops in greater quantity, better quality and faster. The sensors and actuators are assumed as part of these technologiesFrom the physical and environmental data collected by agricultural land sensors (temperature, humidity, etc..) it's possible to monitor all the factors that influence crop growth. Two of the main factors that directly affect crop yields and are present in almost all types of crops are diseases and pests, existing scientific models that perform predictions of the risk of a particular disease or pest affect a crop, based on weather data in the plot of land where each culture is located.Through the actions performed by actuators (irrigation, fertilizer application, etc..), it's possible to obtain control over the environment, keeping these factors in optimum levels for crop development.Given the importance of these technologies, this dissertation focuses on the development of a Framework for the development of applications based on Wireless Sensors and Actuators Networks. Applications built using the Framework should be as generic as they can be in order to be used in all types of crops, while still offering a wide variety of features and a high usability. The Framework aims to overcome some typical problems of development of such applications, which are usually associated with the technological complexity of the devices and systems that support them.